GAMBARAN TINGKAT KEBERSIHAN GIGI DAN MULUT SERTA KARIES GIGI PADA IBU HAMIL YANG BERKUNJUNG KE PUSKESMAS III DENPASAR SELATAN TAHUN 2OI4 - Ni Putu Oki Andreani; Ni Wayan Arini; Sagung Agung Putri Dwiastuti (Jurnal Kesehatan Gigi (Dental Health Journal), 2015)
Group of pregnant women are vulnerable to oral disease. This is due to the increase in estrogen and progesterane that cause nousea and vomiting in the morning (morning sickness). Statistical test found that there was a significant correlation between the frequency of pregnancy, vomiting habit, dental and oral hygiene and dental plaque with the severity if dental caries.This study purpose to describe the level of dentaland oral  hygiene and dental caries among pregnant women who are visiting public health clinic three, south Denpasar in June 2014.  This research is a descriptive study conducted at the health clinic three, South Denpasar in June 2014 with using the total population.The results of the study of 29 pregnant women have the highest percentage of OHI-S  with fair criteria 67,0%. Percentage OHI-S based on the thirds of the month of pregnancy int he trimester l is 66,70%, the second trimester is 75% and the trimester three is 70%. Average OHI-S pregnant women is 2,05. The percentage of pregnant women affected by caries is as much as 75,86% with average caries as much as 1,96. The percentage of dental caries based on the level of dental and oral hygiene have average caries ≥ 2  as many as 16 people with fair criteria. Conclusion is that mojority of pregnant women have criteria of medium OHI-S  and has average caries of low category